Effects of Socioeconomic Conditions on Adolescent Girls’ Menstrual Hygiene Management in Rural India: Understanding the impact of socioeconomic factors on menstrual hygiene management among rural adolescent girls in India (Journal of Advances and Scholarly Researches in Allied Education, 2018)
The objective of the study is to describe the socio - economic background and Menstrual Hygiene Management (MHM)of the adolescent girls in rural areas. Study also assesses the Knowledge, Attitude and Practice about menarche and menstrual hygiene of the adolescent girls, find out the organization between the selected demographic variables amongst the adolescent girls and analyze the efficiency of the planned teaching of menstrual hygiene program on knowledge, attitude and practice.